A comparison of food sources of nudibranch mollusks at different depths off the Kuril Islands using fatty acid trophic markers - Komisarenko,Anatolii; Mordukhovich,Vladimir; Ekimova,Irina; Imbs,Andrey (PeerJ, 2021)
Gastropod molluscs such as nudibranchs are important members of deep-sea benthic ecosystems. However, data on the trophic ecology and feeding specialization of these animals are limited to date. The method of fatty acid trophic markers (FATM) was applied to determine the dietary preferences of nudibranchs off the Kuril Islands. Fatty acid (FA) compositions of Dendronotus sp., Tritonia tetraquetra, and Colga pacifica collected from deep waters were analyzed and compared with those of Aeolidia papillosa and Coryphella verrucosa from the offshore zone. The high level of FATM such as 22:5n-6 and C20 monounsaturated FAs indicated that Dendronotus sp. preys on sea anemones and/or anthoathecates hydroids similarly to that of shallow-water species A. papillosa and C. verrucosa. The high percentage of tetracosapolyenoic acids and the ratio 24:6n-3/24:5n-6 indicated that T. tetraquetra preys on soft corals such as Gersemia and/or Acanella at a depth of 250 m, but soft corals of the family Primnoidae may be the main item in the diet of T. tetraquetra at a depth of 500 m. The high content of Δ 7,13-22:2 and 22:6n-3 shows that C. pacifica can feed on bryozoans. In C. pacifica, 22:5n-6 may be synthesized intrinsically by the mollusks, whereas odd-chain and branched saturated FAs originate from associated bacteria.
Keywords: Nudibranchia; Food webs; Cold-water species; Dietary fatty acids; Lipids